Expression of SUR1 isoforms in the brain and heart after ischemia/reperfusion - Alquisiras-Burgos, Iván; Peralta-Arrieta, Irlanda; Espinoza-Rojo, Mónica; Salazar-Salgado, Alejandro; Antonino-Olguín, Iván; Sánchez-Mendoza, Alicia; Sánchez-Aguilar, María; Ruiz-Tachiquín, Martha-Eugenia; Valdez-Salazar, Hilda-Alicia; Ortiz-Plata, Alma; Franco-Pérez, Javier; Hernández-Cruz, Arturo; et al. (Frontiers in Molecular Neuroscience, 2025)
The sulfonylurea receptor 1 (SUR1) has been classified as a member of the adenosine triphosphate (ATP)-binding cassette (ABC) transporter superfamily. SUR1, unlike the classic ABC transporters, assembles with Kir6.2, forming KATP channels to regulate the flux of potassium ions. In the central nervous system, SUR1 is weakly expressed in some brain regions but is induced by pathological conditions in the different cell types of the neurovascular unit. Therefore, we first analyzed the expression of SUR1 in various rat tissues and brain regions to identify SUR1 isoforms and their mRNA exon composition under physiological conditions. Later, we focused on the SUR1 expression in the brain and heart after ischemia/reperfusion. We observed two SUR1 isoforms (170 and 60–75 kDa) abundantly expressed in most rat tissues, except for the testis and brain, where basal expression of these isoforms was relatively low and exhibit a band of 100 kDa. Every exons coding for the functional domains of SUR1 mRNA were amplified from the tissues and brain regions analyzed. Results from in vitro and in vivo experiments indicated that SUR1 isoforms previously identified (170 and 60–75 kDa) were dramatically overexpressed in the brain after middle cerebral artery occlusion followed by reperfusion. In contrast, myocardial infarction followed by reperfusion significantly reduced SUR1 isoform expression in the heart. This study demonstrates the expression of at least two SUR1 isoforms in various tissues and suggests that ischemic processes may differentially regulate SUR1 expression depending on the tissue injured.